Imaging zebrafish neural circuitry from whole brain to synapse - Leung, Louis C.; Wang, Gordon X.; Mourrain, Philippe (Frontiers in Neural Circuits, 2013)
Recent advances in imaging tools are inspiring zebrafish researchers to tackle ever more ambitious questions in the neurosciences. Behaviorally fundamental conserved neural networks can now be potentially studied using zebrafish from a brain-wide scale to molecular resolution. In this perspective, we offer a roadmap by which a zebrafish researcher can navigate the course from collecting neural activities across the brain associated with a behavior, to unraveling molecular identities and testing the functional relevance of active neurons. In doing so, important insights will be gained as to how neural networks generate behaviors and assimilate changes in synaptic connectivity.